Multi-Domain Authentication Protocol Based on Dual-Signature - Zengyu Cai; Qikun Zhang; Ming Li; Yong Gan; Junsong Zhang (Universitas Ahmad Dahlan, 2015)
Today most multi-domain networks authentication systems provide data security and mutual authentication with asymmetric and traditional public key cryptography., there exist some problems, such as the overhead of passing certificates, the more complexity of management certificates and network bottlenecks and so on. These schemes can’t protect the safety of multi-domain interoperability in distributed network effectively. Aiming at these problems, the paper proposes an identity-based multi-domain authentication protocol among domains in large-scale distributed collaborative computing network. It adopts bilinear mapping and short signature technology to achieve mutual authentication between entities in different domains, which overcome the complexity of certificate transmission and bottlenecks in the scheme of PKI-based. Analyzed shows that this scheme has anonymity, security and supporting mutual anonymous authentication and it is suitable to use in security alliance authentication mechanism in large distributed network.